ANALISIS KONSTRUKSI SINTAKSIS PADA SLOGAN KULINER - Nanda Riska Dwi Aprila; Nurul Fauziyah (Jurnal Komposisi, 2021)
This research was conducted to describe the forms of syntactic construction or syntactic tools in several culinary slogans. This study uses a qualitative descriptive approach, because this study will describe the forms of syntactic construction categories in culinary slogans on social media or print media and analyze the syntactic constructions on these culinary slogans. The data in this study are based on written data sources in the form of phrases, clauses, sentences, and the discourse of the culinary slogans that have been collected. This study uses documentation techniques, namely by listening, recording, and classifying the forms of syntactic construction found in culinary slogans to collect data. The analysis technique in this study uses a distributional basic technique, namely the Direct Elements Sharing Technique (BUL) (Segmenting Immediate Constituens Techniques) which is used to categorize a construction on the direct elements that make up the construction and the orthographic equivalent method or written language because it is based on the determining tool part of the language studied. in the form of written language, namely culinary slogans. So it is intended to examine the forms of syntactic construction in culinary slogans on social media or print media.